Konsep Perlindungan Hukum Terhadap Buruh Yang Mendapatkan Pemutusan Hubungan Kerja Akibat Covid-19 - Suci Mahara; Malahayati M; Hasan Basri (Fakultas Hukum Universitas Malikussaleh, 2021)
The entry of Corona Virus Disease (Covid-19) in early March 2020 to Indonesia, forced companies / employers to forcibly lay off workers / laborers due to the non-operation of the company and obeying the regulations issued by the government regarding the prohibition of gathering and maintaining distance from each other. The formulation of the problem in this research is the concept of legal protection for workers who have been laid off due to Covid-19 which is reviewed through Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation. The purpose of this study is to describe and provide an overview of legal protection for workers who have been laid off due to this pandemic. This research method is a qualitative method with a normative form of research that puts laws or rules to answer the problems to be studied. The approach in this research comes from statutory regulations and literature study. Based on the results of this study, the concept of legal protection for workers who were laid off due to Covid-19 which was reviewed through the Manpower Act is based on Pancasila which includes legal protection for wages, welfare and social security for workers and the concept of legal protection for workers who have been laid off as a result of Covid-19 based on the Job Creation Law, namely equal justice by giving severance pay as the fulfillment of labor rights. This study advises the government to include specific rules regarding legal protection for workers who have been laid off due to disease outbreaks and advises employers / employers to include the rights that workers need in the work agreement if a forced layoff occurs. Key Words: Legal Protection, Covid-19, PHK.